COMPARATIVE ANALYSIS OF SELECTION OF SHARIA PUBLIC SAVINGS AND QURBAN SAVINGS PRODUCTS IN KOPSYAH MUI JATIM BRANCH SEKAPUK - rohmah, mazidatur; Muhammad Ala’uddin; Dwi Afrianti (Universitas Muhammadiyah Surabaya, 2025)
This study presents a comparative analysis of the selection of Sharia General Savings and Qurban Savings at KOPSYAH MUI East Java, Sekapuk Branch, with a case study on members of Bolo Village, Ujungpangkah. The objective is to identify the factors influencing members' preferences for both products. The research employed a qualitative comparative approach with descriptive-analytical methods, and data validity was ensured through triangulation techniques. The findings reveal that the factors influencing product selection include: (1) internal factors such as family, motivation, involvement, and age groups that shape social influence; (2) external factors such as product quality, profit-sharing system, location, and service, including a door-to-door service that facilitates transactions. This study presents a comparative analysis of the selection of Sharia General Savings and Qurban Savings at KOPSYAH MUI East Java, Sekapuk Branch, with a case study on members of Bolo Village, Ujungpangkah. The objective is to identify the factors influencing members' preferences for both products. The research employed a qualitative comparative approach with descriptive-analytical methods, and data validity was ensured through triangulation techniques. The findings reveal that the factors influencing product selection include: (1) internal factors such as family, motivation, involvement, and age groups that shape social influence; (2) external factors such as product quality, profit-sharing system, location, and service, including a door-to-door service that facilitates transactions.